Electrohydraulic thrust vector control of twin rocket engines with position feedback via angular transducers - LAZIC, Dragan V; RISTANOVIC, Milan R (Control engineering practice, 2007)
The thrust vector control (TVC) of rocket engines is used when the aerodynamic surfaces are inadequate to control vehicles or when a greater agility may be required of a missile. Traditionally, in all spacecraft to date actuators used to gimbal the engine have been hydraulic. The subject of this paper is the TVC with gimballed nozzle assembly controlled by an electrohydraulic servosystem, where two linear hydraulic servoactuators gimbal the engine. Each servoactuator is controlled by an electrohydraulic servovalve. The thrust vector direction is a result of the motion of both servoactuators. In this paper the TVC system is treated as a robotic system that allows developing the procedure of solving an inverse kinematics problem as well as the control of the robotic system in the output space instead of in the space of internal dynamics. The position feedback is provided by measuring the direction of the thrust vector, instead of measuring the displacements of the servoactuators. A linear model of the servosystem has been developed and simulated. The proposed control concept has experimentally been validated in the TVC test bench.